Molecular and Functional Analysis of Pore-Forming Toxin Monalysin From Entomopathogenic Bacterium Pseudomonas entomophila - Nonaka, Saori; Salim, Emil; Kamiya, Koki; Hori, Aki; Nainu, Firzan; Asri, Rangga Meidianto; Masyita, Ayu; Nishiuchi, Takumi; Takeuchi, Shoji; Kodera, Noriyuki; Kuraishi, Takayuki (Frontiers in Immunology, 2020)
Pseudomonas entomophila is a highly pathogenic bacterium that infects insects. It is also used as a suitable model pathogen to analyze Drosophila's innate immunity. P. entomophila's virulence is largely derived from Monalysin, a β-barrel pore-forming toxin that damages Drosophila tissues, inducing necrotic cell death. Here we report the first and efficient purification of endogenous Monalysin and its characterization. Monalysin is successfully purified as a pro-form, and trypsin treatment results in a cleaved mature form of purified Monalysin which kills Drosophila cell lines and adult flies. Electrophysiological measurement of Monalysin in a lipid membrane with an on-chip device confirms that Monalysin forms a pore, in a cleavage-dependent manner. This analysis also provides a pore-size estimate of Monalysin using current amplitude for a single pore and suggests lipid preferences for the insertion. Atomic Force Microscope (AFM) analysis displays its structure in a solution and shows that active-Monalysin is stable and composed of an 8-mer complex; this observation is consistent with mass spectrometry data. AFM analysis also shows the 8-mer structure of active-Monalysin in a lipid bilayer, and real-time imaging demonstrates the moment at which Monalysin is inserted into the lipid membrane. These results collectively suggest that endogenous Monalysin is indeed a pore-forming toxin composed of a rigid structure before pore formation in the lipid membrane. The endogenous Monalysin characterized in this study could be a desirable tool for analyzing host defense mechanisms against entomopathogenic bacteria producing damage-inducing toxins.